2017
DOI: 10.18632/oncotarget.22247
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-4 is essential for saikosaponin a-induced apoptosis acting upstream of caspase-2 and γ-H2AX in colon cancer cells

Abstract: Saikosaponin a (SSa), a bioactive phytochemical from Bupleurum, triggers sequential caspase-2 and caspase-8 activation, and thereby induces caspase-mediated apoptosis in human colon carcinoma (HCC) cells. However, the upstream mechanism of caspase-2 activation remains unknown. Therefore, we investigated the signaling mechanisms underlying SSa-induced caspase activation and apoptosis in HCC cells. SSa treatment triggered marked antitumor effects, especially in HCC cells, in a cell culture model and a mouse xeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…Saikosaponins exert significant pharmacological activities, including antitumor, chemosensitizing, radiosensitizing, anti‐inflammatory, hepatoprotective, nephroprotective, anti‐Alzheimer, neuroprotective, immune‐modulatory, anti‐virus, and so on. Saikosaponins are considered to be the major bioactive ingredients and the key markers for quality control of Radix Bupleuri , which is a famous traditional Chinese medicine (TCM) that has been used for more than 1000 years.…”
Section: Introductionmentioning
confidence: 99%
“…Saikosaponins exert significant pharmacological activities, including antitumor, chemosensitizing, radiosensitizing, anti‐inflammatory, hepatoprotective, nephroprotective, anti‐Alzheimer, neuroprotective, immune‐modulatory, anti‐virus, and so on. Saikosaponins are considered to be the major bioactive ingredients and the key markers for quality control of Radix Bupleuri , which is a famous traditional Chinese medicine (TCM) that has been used for more than 1000 years.…”
Section: Introductionmentioning
confidence: 99%
“…Excessive DNA damage may induce γ-H2AX-positive cells to undergo apoptosis and exert protective roles [40]. Also, Saikosaponin a (SSa) was reported to induce caspase-mediated apoptosis in human colon carcinoma cells by triggering DNA damage, as evidenced by an increase in the levels of γ-H2AX [41]. Thus, TSSK6 may inhibit HCV-HCC progression by [45].…”
Section: Discussionmentioning
confidence: 99%
“…SSa, SSd, 6″-O-acetylsaikosaponin-d and 23-hydroxy-13β, 28β-epoxy-olean-11-ene-16-one-3-O-β-d-glu-copyranosyl-(1→3)-β-d-fucopyranoside exhibit more potent cytotoxicity than other SS derivatives, and are even more cytotoxic against human hepatoma HepG2 cells and human lung cancer A549 cells than the positive control, 5-fluorouracil . A recent study suggested that human colon cancer cells, but not lung cancer, breast cancer and leukemia cells, are sensitive to SSa-induced apoptosis (Kang et al, 2017). Caspase-4 and downstream sequential caspase-2/caspase-8 activation is suggested to be essential for anticancer effects of SSa on human colon cancer cell lines (Kang et al, 2017;Kim and Hong, 2011).…”
Section: Effects Of Sss On Cancersmentioning
confidence: 99%
“…A recent study suggested that human colon cancer cells, but not lung cancer, breast cancer and leukemia cells, are sensitive to SSa-induced apoptosis (Kang et al, 2017). Caspase-4 and downstream sequential caspase-2/caspase-8 activation is suggested to be essential for anticancer effects of SSa on human colon cancer cell lines (Kang et al, 2017;Kim and Hong, 2011). Several studies further suggested that SSa induces apoptosis in human breast MDA-MB-231 and MCF-7 cells via p53/p21 independent and dependent mechanisms respectively and inhibits the growth of HepG2 by induction of CDK inhibitors Wu and Hsu, 2001).…”
Section: Effects Of Sss On Cancersmentioning
confidence: 99%